A modern view of the problem of teething abnormalities (Literature review) Introduction. - Malashenko, Н. Ю. (Actual Dentistry, 2024)
Timely tooth eruption is one of the most important indicators of the proper functioning of the dentition, which not only determines the correct position of the teeth in the dentition, but also have a significant impact on the condition of the occlusal relations, the temporomandibular joint, the periodontal tissues, the functioning of the facial and chewing muscles, the height of the lower third of the face, and the aesthetic smile. Aim: To determine the prevalence and aetiological causes of teething abnormalities based on a literature review. Materials and Methods. The information search and analysis of scientific sources was performed using the scientometric databases Web of Science, PubMed, Google Scholar for the last 15 years. Conclusion. Despite the fact that delayed teething is uncommon, this pathology should be diagnosed and treated in time to avoid potential negative effects on masticatory function, aesthetics, confidence, mental health and speech. To sum up, the literature data suggests that appropriate diagnosis and treatment of delayed eruption, including consideration of developmental factors, may help to ensure optimal long-term outcomes and prevent recurrence.